Pembentukan Karakter Siswa Dengan Menggunakan Metode Pembelajaran Ekspositori Pada Mata Pelajaran Sejarah: Indonesia - Mirza Karno Sarmidi; Fahruddin (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
This study aims to analyze the effectiveness of expository learning strategies in shaping students’ characters at the high school level through history subjects, with a focus on the internalization of moral values. This study uses qualitative methods and the collection technique uses library research methods by reviewing previous sources. The results of the study indicate that expository strategies are effective in transferring basic historical knowledge and shaping characters through the integration of moral values, although the risk of students having passive nature in learning can be overcome by a combination of interactive elements. The conclusion of this study states that expository is not only effective for mastering academic content but also crucial in developing students’ ethical character; the novelty of this study lies in the integrative approach that combines expository with specific character formation in the context of Indonesian high schools in the era of globalization.